An investigation of the corrosion inhibitive layers generated from lithium oxalate‐containing organic coating on AA2024‐T3 aluminium alloy. (7th March 2016) - Liu, Yanwen; Visser, Peter; Zhou, Xiaorong; Lyon, Stuart B.; Hashimoto, Teruo; Gholinia, Ali; Thompson, George E.; Smyth, Gerard; Gibbon, Simon R.; Graham, Derek; Mol, Johannes M. C.; Terryn, Herman
Abstract : The protective film formed in a defect by leaching of lithium oxalate from model organic coatings during neutral salt spray exposure has been investigated. A scribed area of about 1 mm width was introduced on the coated AA2024‐T3 aluminium alloy. The scribed area was examined before and after exposure in neutral salt spray environment for 4, 8, 24 and 168 h by scanning and transmission electron microscopies. It was found that the lithium oxalate was able to leach from the organic coating during neutral salt spray exposure and it promoted the formation of a film that provided effective corrosion protection to the alloy. The typical film morphology consists of three different layers, including a relatively compact layer near the alloy substrate, a porous middle layer and a columnar outer layer. Variation of the film morphology was also observed at different locations of the scribed alloy surface, which may be related to the difference of local concentration of lithium species. Electron energy loss spectroscopy detected lithium, aluminium and oxygen in the film. Although the film showed the varied morphologies in different regions of the scribed area, the alloy substrate was protected from corrosion when the film was formed. Copyright © 2016 John Wiley & Sons, Ltd.